The economic burden of metastatic breast cancer in Spain. Issue 1 (30th July 2018) - Bermejo de las Heras, Begoña; Cortes Ramon y Cajal, Javier; Galve Calvo, Elena; de la Haba Rodriguez, Juan; Garcia Mata, Jesus; Moreno Anton, Fernando; Pelaez Fernandez, Ignacio; Rodriguez-Lescure, Alvaro; Rodriguez Sanchez, Cesar A; Ruiz-Borrego, Manuel; Remak, Edit; Barra, Magdolna; et al.
Abstract : Objectives: The study aimed to estimate the burden of metastatic breast cancer (mBC) in Spain over 5 years. Methods: An incidence-based cost-of-illness model was developed in which a cohort of patients with mBC was followed from the diagnosis of metastatic disease over 5 years or death. Resource use data were collected through a physician survey conducted with 10 clinical experts in Spain. The model distinguished patients according to HER2 and hormonal receptor (HR) status, and followed the patient cohort in monthly cycles. Results: The incident cohort was estimated to be 2, 923 patients with mBC, consisting of 1, 575 HER2−/HR+, 520 HER2+/HR+, 324 HER2+/HR−, and 503 triple negative patients. The estimated mean survival over the 5-year time period was 2.51 years, on average, with longer survival of 3.36 years for HER2+/HR+, 2.41 years for HER2−/HR+, 2.82 years for HER2+/HR− and shortest mean survival of 1.74 years for triple negative patients. The total costs were €469, 92, 731 for the overall population, €190, 079, 787 for the HER2-/HR+, €151, 045, 260 for the HER2+/HR+, €80, 827, 171 for the HER2+/HR- and €47, 540, 512 for the triple negative subgroups over 5 years. Per patient total costs were €160, 642 on average, €120, 664 for HER2-/HR+, €290, 346 for HER2+/HR+, €249, 152 for HER2+/HR−and €94, 572 for triple negative patients over 5 years. Conclusions: The economic burden of mBC in Spain is significant, but differs by HER2 and HR status. HER2−/HR +patients account for the highest burden due to the prevalence of this category, but HER2+/HR +patients have the highest per patient costs.